2022
DOI: 10.3390/ijms23179685
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Curcumin and Ferulic Acid Suppressed the Aβ-Induced Neurotoxicity More than Curcumin and Ferulic Acid Alone

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease that leads to progressive cognitive decline. Several effective natural components have been identified for the treatment of AD. However, it is difficult to obtain conclusive evidence on the safety and effectiveness of natural components, because a variety of factors are associated with the progression of AD pathology. We hypothesized that a therapeutic effect could be achieved by combining multiple ingredients with different efficacies. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…They showed diverse biological activity related to neurodegenerative disorder including AD. Cymserine ( 6 ), huperazine ( 7 ), ferulic acid (FA, 8 ), curcumin (CUR, 9 ), Phenserine ( 10 ), and velnacrine ( 11 ) are the example of some natural products that directly or indirectly improve learning and memory in AD by acting on ChE, Aβ, and oxidative stress hypothesis (Ohashi et al., 2022; Qian & Ke, 2014).…”
Section: Current Treatment For Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…They showed diverse biological activity related to neurodegenerative disorder including AD. Cymserine ( 6 ), huperazine ( 7 ), ferulic acid (FA, 8 ), curcumin (CUR, 9 ), Phenserine ( 10 ), and velnacrine ( 11 ) are the example of some natural products that directly or indirectly improve learning and memory in AD by acting on ChE, Aβ, and oxidative stress hypothesis (Ohashi et al., 2022; Qian & Ke, 2014).…”
Section: Current Treatment For Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Additionally, FA pretreatment of SH-SY5Y cells inhibited the transition of Aβ 42 from monomers to oligomers by preventing Aβ 42 from forming fibrils [ 165 ]. Similarly, another study in SH-SY5Y cells examined the effect of FA on Aβ 1–40 -induced hallmarks of AD such as Aβ aggregation, cell death, and ROS formation, and reported significant decreases in Aβ aggregation and intracellular and mitochondrial ROS formation, as well as membrane damage repair [ 166 ]. A comparable study revealed that the anti-inflammatory effect of FA in LPS-stimulated BV-2 microglial cells was mediated via significant suppression of IL-1β, prostaglandin E2 (PGE2), and NO release, a reduction of COX-2 and iNOS expression, and the subsequent inhibition of TLR4 activity in a concentration-dependent manner [ 167 ].…”
Section: Dietary Small Molecules and Neuroprotection – A Overview Of ...mentioning
confidence: 99%
“…Ohashi et al reported that FA combination with curcumin treatment was confirmed to effectively inhibit Aβ aggregation, decrease mitochondrial and extracellular ROS levels by increasing the cell viability, and improve the mitochondrial function in Aβ exposure SH-SY5Y cells. Combination treatment produced an overall higher neuroprotective effect than treatment with FA or curcumin alone [ 166 ]. In another study, it was found that a combination treatment of FA, atractylenolide III, and paeoniflorin can exert neuroprotective and anti-inflammatory effects on LPS-induced autophagy and neuroinflammation in BV-2 microglial cells by significantly increasing the expression of autophagy-related proteins p-AMPK, Beclin1, p-ULK1, LC3, and TFEB and decreased the expression of p62 and significantly reduced the production of inflammatory factors such as IL-6, IL-1β, and TNF-α [ 168 ].…”
Section: Combination Therapeutic Effects Of Dietary Small Molecules I...mentioning
confidence: 99%
“…It is now well established that the level of oxidation in the brain also increases with age [ 178 ]. Interestingly, extensive oxidative damage can be observed in the stage of mild cognitive impairment that precedes the typical clinical manifestations of AD, suggesting that oxidative stress may be a central mechanism in driving the disease [ 179 ].…”
Section: Mechanism Of Saponins In Treating Alzheimer’s Diseasementioning
confidence: 99%